Media discussion and public opinion: reflections in the Brazilian criminal persecution system (Research, Society and Development, 2022)
This article analyzed the interference of public opinion when an administrative or judicial decision is made, within the scope of Brazilian criminal prosecution. We used case studies as a strategy, collecting data through documentary research. Three cases with great media repercussion were selected and analyzed, being: TJSP Case No. 0002554-94.2003.8.26.0100, called Caso Escola de Base; TJSC Case - No. 0000568-40.2019.8.24.0023, named as Case Elian Lucas Ferreira Dias; and TJRJ Process – no. 0012515-98.2019.8.19.0001, referred to as Leonardo do Nascimento dos Santos Case. To analyze the cases, the legal bases concerning each one was exposed, based on the legislation, doctrine, and Brazilian jurisprudence. The results allow us to conclude that the procedural decision-making of both cases analyzed was marked by the external influence arising from the public opinion generated and fostered by the Mass Media, which had an impact on the criminal prosecution of the cases. It is concluded that the media does not only influence the population in general once that media agencies end up interfering in the achievement of exclusive State activities.